A Survey of Knowledge and Use of Academic Library Services at a Pseudo-Satellite Location - Lee, Jason; Head, Rachel; Vienneau, Courtney; Hoover, Jasmine; Chandler, Martin (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – Following a rapid increase in student population over a five-year period, Cape Breton University leased additional teaching space from a nearby cinema chain but did not account for students’ library needs. The local nature of the venue, combined with issues in transit to the main campus, created “local-distance” students. These students were surveyed on awareness and use of library resources and services to inform future services.Methods – Students whose classes were primarily located at the cinema chain were engaged in an anonymous survey regarding their knowledge and use of library services. These data were then analyzed for common themes and recommendations.Results – There were notable gaps in student knowledge and use of library resources and services, perhaps owing to the primary source of information regarding these – namely, friends, professors, and the website. The need for further outreach and onsite library workers was highlighted, as was the importance of library as space.Conclusion – While the library handled the new venue as well as possible, it is crucial for administrators involved in change management to remember that student learning involves more than individuals in a classroom seat.